Interface engineering and characterization at the atomic‐scale of pure and mixed ion layer gas reaction buffer layers in chalcopyrite thin‐film solar cells. (11th March 2014) - Cojocaru‐Mirédin, Oana; Fu, Yanpeng; Kostka, Aleksander; Sáez‐Araoz, Rodrigo; Beyer, Andreas; Knaub, Nikolai; Volz, Kerstin; Fischer, Christian‐Herbert; Raabe, Dierk
Abstract: In this work, we investigate the p–n junction region for two different buffer/Cu(In, Ga)(Se, S)2 (CIGSSe) samples having different conversion efficiencies (the cell with pure In2 S3 buffer shows a lower efficiency than the nano‐ZnS/In2 S3 buffered one). To explain the better efficiency of the sample with nano‐ZnS/In2 S3 buffer layer, combined transmission electron microscopy, atom probe tomography, and X‐ray photoelectron spectroscopy studies were performed. In the pure In2 S3 buffered sample, a CuIn3 Se5 ordered‐defect compound is observed at the CIGSSe surface, whereas in the nano‐ZnS/In2 S3 buffered sample no such compound is detected. The absence of an ordered‐defect compound in the latter sample is explained either by the presence of the ZnS nanodots, which may act as a barrier layer against Cu diffusion in CIGSSe hindering the formation of CuIn3 Se5, or by the presence of Zn at the CIGSSe surface, which may disturb the formation of this ordered‐defect compound. In the nano‐ZnS/In2 S3 sample, Zn was found in the first monolayers of the absorber layer, which may lead to a downward band bending at the surface. This configuration is very stable (Fermi level pinning at the conduction band, as observed for Cd in Cu(In, Ga)Se2 ) and reduces the recombination rate at the interface. This effect may explain why the sample with ZnS nanodots possesses a higher efficiency. This work demonstrates the capability of correlative transmission electron microscopy, atom probe tomography, and X‐ray photoelectron spectroscopy studies in investigating buried interfaces. The study provides essential information for understanding and modeling the p–n junction at the nanoscale in CIGSSe solar cells. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : Electrical properties, structure, and chemical composition of two different buffer/Cu(In, Ga)(Se, S)2 samples, pure In2 S3 and nano‐ZnS/In2 S3, are investigated by means of a solar simulator, high‐resolution scanning transmission electron microscopy, atom probe tomography, and X‐ray photoelectron spectroscopy. The sample containing the ZnS nanodots possesses the highest efficiency, and this is explained by the Zn diffusion within the first monolayers of the absorber layer leading to a downward band bending at the surface. This configuration is very stable (Fermi level pinning at the conduction band, as observed for Cd in Cu(In, Ga)Se) and reduces the recombination rate at the interface.